A Comparison of Anterior Cervical Corpectomy and Fusion Combined With Artificial Disc Replacement and Cage Fusion in Patients With Multilevel Cervical Spondylotic Myelopathy. Issue 16 (15th August 2015) - Mao, Ningfang; Wu, Jinhui; Zhang, Ye; Gu, Xiaochuan; Wu, Yungang; Lu, Chunwen; Ding, Muchen; Lv, Runxiao; Li, Ming; Shi, Zhicai
Abstract : Study Design: A retrospective study. Objective: The aim of this study was to compare clinical and radiological outcomes of anterior cervical corpectomy and fusion (ACCF) combined with artificial disc replacement (C-ADR) and ACCF combined with anterior cervical discectomy and fusion (ACDF) in patients with consecutive 3-level cervical spondylotic myelopathy (CSM). Summary of Background Data: The optimal surgical strategy for multilevel CSM (MCSM) remains undefined. C-ADR maintains motion at the level of the surgical procedure and decreases strain on the adjacent segments. The clinical results of multilevel C-ADR have not yet been elucidated. ACCF combined with 1-level C-ADR for the treatment of consecutive 3-level CSM may be a reasonable alternative to 3-level fusion. Methods: We retrospectively reviewed the histories of patients who underwent surgery for consecutive 3-level CSM between C3–4 and C6–7 from June 2007 to August 2011. A total of 42 patients were divided into 2 groups. Group A (n = 19) underwent ACCF combined with 1-level C-ADR; group B (n = 23) underwent ACCF combined with 1-level ACDF. We compared perioperative parameters, clinical parameters, and radiological parameters. Results: There were no significant differences in the average age, sex ratio, the preoperative heights of the disc space or average blood loss between the 2 groups. Group A had longer operation times than group B ( P < 0.05). During the follow-up period, group A showed a better Neck Dysfunction Index recovery ( P < 0.05) at 24 months postoperatively, and less visual analogue scale scores at 12 and 24 months postoperatively ( P < 0.05 and P < 0.001, respectively). Moreover, group A exhibited better C2–C7 range of motion recovery at 6, 12, and 24 months postoperatively ( P < 0.05, respectively). Conclusion: Group A was superior to Group B in terms of better Neck Dysfunction Index recovery, less intermediate term pain, and better C2–C7 ROM recovery. ACCF hybrid 1-level C-ADR may be a suitable choice for the management of 3-level CSM in appropriate patients. Level of Evidence: 3 Abstract : The clinical and radiological outcomes of anterior cervical corpectomy and fusion (ACCF) combined with artificial disc replacement and ACCF combined with anterior cervical discectomy and fusion were compared in patients with consecutive 3-level cervical spondylotic myelopathy. ACCF combined with 1-level artificial disc replacement for the treatment of consecutive 3-level cervical spondylotic myelopathy may be a reasonable alternative to 3-level fusion.